Egg Yolk as pore creating agent to produce porous tri-calcium phosphate for bone implant application - Abdul Rahman, Fariza; Ahmad, Zuraida; Iis, Sopyan (Trans Tech Publications, 2011)
Porous tri-calcium phosphate which is to be applied as artificial bone was prepared via protein consolidation method and egg yolk is used to give binding effect as well as to create porosity. In this experiment, fractions of egg yolk is controlled from 50 wt%, 60 wt%, 70wt% and 80 wt% and the mixture of egg yolk and tri-calcium phosphate powder were dried at 60 °C before undergone uniaxial compaction method. Subsequently, pressure of 68.5 MPa is given to the mold to produce cylindrical shape samples with diameter to height ratio of 1:2. Samples were then sintered at 1100°C to achieve porous tri-calcium phosphate. This method produced porous tri-calcium phosphate with desired porosity of 20-54.5% and acceptable compressive strength between 0.7-0.07 MPa. Besides, microporosity of 0.4-1μm and macroporosity in the range of 100-800μm were successfully obtained from this method.